At the heart of harm: Cardiac substrates of action-based aversion to harm. (1st December 2019) - Parton, Drew M.; McGinley, Jared J.
Abstract: Facets of cardiovascular functioning have been used to index pro-social attitudes and behaviors. A recent study found that participants who engaged in prototypically (yet harmless) violent acts showed a vascular stress response, suggesting that individuals find some acts immoral even without harmful consequences (Cushman et al., 2012). The present research replicates and expands upon that study by (1) utilizing beta-adrenergic and vagally-mediated cardiac markers of actions, (2) assessing the aversiveness of each individual action, and (3) validating a trait-like measure of action aversion. Participants performed either a series of simulated acts of harm or physically identical (but emotionally neutral) actions. Overall, participants reported greater negative reactions to the aversive acts compared to physically identical neutral acts. In addition, sympathetically-mediated cardiac responses were observed for participants who performed simulated acts of harm. However, the vagally-mediated measure of cardiac activity did not significantly predict self-reported aversion to performing actions. The present study partially validates the paradigm introduced in Cushman et al. (2012) and provides further evidence that some individuals have an automatic adverse reaction to prototypical acts of harm in and of themselves. It also highlights the limitations of using vagally-mediated markers to index self-regulation or pro-social attitudes. Highlights: Action aversion to harm can be captured by self-report and physiology. Resting heart rate variability is not a significant predictor of action aversion. Not all acts in the current paradigm for action aversion are viewed as aversive.